Virality of Photojournalism as A Development Communication Strategy: A Documentary Study of Raisan Al Farisi at Sukaluyu Bridge, Cianjur - Suherlan, Ryan; Darmawan, Ferry; Gani, Rita (Institut Agama Islam Negeri (IAIN) Manado, 2025)
This article analyzes how the virality of photojournalistic images can serve as an effective development communication strategy in the digital age. The case examined is the work of Raisan Al Farisi documenting the struggles of elementary school children in Sukaluyu Village, Cianjur Regency, who crossed a river without a bridge in order to attend school. The photograph went viral on social media and ultimately prompted the government to construct a bridge at that location. This study employs a qualitative approach using a case study method and the social semiotic theory of Kress and van Leeuwen. The findings indicate that three semiotic meanings are embedded in Raisan Al Farisi’s photographic work. First, Representational Meaning: the photograph presents the social reality of rural children facing risks and unequal access to education, with the act of crossing the river becoming a symbol of struggle and hope for the future. Second, Interactive Meaning: the use of an eye-level angle constructs a strong emotional connection between the photographic subject and the audience, transforming viewers from passive observers into active participants in the children’s experience. Third, Compositional Meaning: the diagonal structure and color contrast between the red-and-white uniforms and the river water create visual tension that directs attention toward the meaning of struggle, emphasizing the message that education demands courage and sacrifice. Raisan Al Farisi’s photograph demonstrates that visual power can mobilize public awareness and serve as a catalyst for tangible change in social development.